Poverty and Inequality in India A Survey of Literature and Policy Issues - Planning Commission (Planning Commission, 1982)
Dr. Tarun Kanti Das’s survey examines poverty and inequality in India, analyzing historical trends, measurement challenges, and policy implications. Key issues include defining income, selecting appropriate demographic units, and measuring poverty and inequality using tools like the Gini coefficient. Studies show persistent income and wealth disparities, with rural poverty linked closely to agricultural performance and significant regional variations across states. While rural poverty declined between 1956 and 1974, urban poverty remained stable. The report emphasizes the need for targeted redistributive policies, improved measurement methodologies, and integration of economic growth with social justice. Recommendations include addressing regional inequalities, enhancing access to education, health, and employment, and implementing policies aligned with local realities. Overall, the study underscores that effective poverty reduction requires multi-faceted interventions supported by continuous research and robust statistical analysis.
Government of India Planning Commission UNDP Transport Policy Planning Project, Yojana Bhawan, New Delhi 110001 April, 1982
Government of India Planning Commission UNDP Transport Policy Planning Project, Yojana Bhawan, New Delhi 110001 April, 1982
Keywords: Poverty; Inequality; Income Distribution; Rural Development; Socio-Economic Disparities; Measurement Methodologies; Policy Interventions; Regional Disparities; Gini Coefficient; Agricultural Productivity; Social Justice; Poverty Alleviation